Desain Pembelajaran Matematika Berbasis Hypothetical Learning Trajectory (HLT) Pada Materi Operasi Bilangan Bulat Siswa Kelas VII SMP Bunda Kasih Sudiang - Christian Moanoang; Nurdin Arsyad; Nasrullah (Issues in Mathematics Education (IMED), 2021)
This research aims to produce a design-based Hypothetical Learning Trajectory (HLT) learning in the integer’s operations materials that can make class VII students understand the integer’s operations materials and resolve issues related to integer’s operations. The type of research used is Design Research. The subject of this study was a grade VII junior high students. In this research, researchers made HLT the earliest suspect of the learning activity carried out in two test cycles until the expected learning design was obtained. The results of a retrospective analysis showed that the design of learning was compiled to provide positive changes to class VII junior high students in understanding the concept of integer’s operations. From the work of several groups, the majority of students have achieved the learning objectives, namely understanding integers, determining the sum of integers, determining the reduction of integers and solve daily problems relating to integer’s operations. The work of students are accompanied by conjectures that occur or do not occur in the learning process that has been compiled in HLT.